Peripheral markers of vascular endothelial dysfunction show independent but additive relationships with brain‐based biomarkers in association with functional impairment in Alzheimer's disease: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Drake, Jonathan D.; Chambers, Alison; Ott, Brian R.; Daiello, Lori A.
Abstract: Background: Current epidemiologic evidence suggests that potentially modifiable midlife vascular risk factors specifically influence propensity for later‐life Alzheimer's disease (AD)‐associated cognitive decline. Despite this, a large knowledge gap still exists with respect to characterization of the biological overlap of highly co‐morbid vascular and AD pathologies in clinical AD. Prior studies focusing on contributions of co‐existing imaging‐based white matter disease and amyloid burden have found independent and/or additive rather than interactive associations to risk for cognitive decline, however recent studies utilizing sensitive measures of vascular dysfunction or expanded panels of AD pathology indicate that more nuanced synergistic associations between these pathologies may exist in AD. We hypothesized that elevated plasma cell adhesion molecule (CAM) levels would correlate with severity of diagnosis and functional impairment in AD dementia and be concomitantly lower in mild cognitive impairment (MCI) and normal controls, respectively, and would act synergistically rather than independently with CSF AD biomarkers in this regard. Method: Using generalized linear regression models, we examined cross‐sectional relationships of plasma vascular cell adhesion molecule‐1 (VCAM‐1), intercellular adhesion molecule‐1 (ICAM‐1), and E‐Selectin to baseline diagnosis and functional impairment staging (clinical dementia rating sum‐of‐boxes, CDR‐SB) in the Alzheimer's Disease Neuroimaging (ADNI) cohort (n=564). We also assessed for modifying effects of AD risk factors including ApoE‐ε4 genotype, and then tested for interactive association by combining CAMs with CSF biomarkers into CDR‐SB models in a subset with available CSF data (n=351). Result: Higher mean VCAM‐1 (p=0.0026) and ICAM‐1 (p=0.0189) levels were found in AD versus MCI groups, however not in MCI versus cognitively normal groups. Only VCAM‐1 was linked with CDR‐SB scores (p=0.0157), and ApoE‐ε4 genotype modified this effect (p < 0.0001). Contrary to our expectation, we observed independent and additive rather than interactive associations of VCAM‐1 and CSF Aβ42, total tau, phosphorylated tau (P‐tau), and P‐tau/Aβ42 (all < p=0.01) in a combined CDR‐SB model (and ICAM‐1 to a lesser extent). Conclusion: Our findings indicate independent rather than synergistic associations of plasma‐based biomarkers of vascular endothelial dysfunction and CSF biomarkers of AD pathology and neurodegeneration with AD‐related clinical impairment. Future longitudinal studies will be needed to validate these findings.